Gobernanza en México (1996-2020) con base en los índices de eficacia del gobierno y calidad regulatoria (Tema Central) - Torres Fragoso, Jaime (2024)
If the authorities in Latin America have low approval levels, this research assesses the performance of the government of Mexico over the last 25 years with two key indicators of the new political governance, analyzing the absolute and relate positions of Mexico in the efficiency indexes of the government and regulatory quality through the Worldwide Governance Indicators (WGI) platform. The theoretical framework is made up by the governance model proposed by two administration philosophies that have a noteworthy connection with public management and new public management. The results show that, for the administration periods of Ernesto Zedillo, Vicente Fox and Felipe Calderón, the records could be considered positive and associated to appropriate management practices. Similarly, the performance for the government led by Enrique Peña Nieto and the one led by Andrés Manuel López Obrador are not favorable; the explanative variables of this results are also presented. The research concludes by stating that the use of indicators and models, while certainly important, only represents strategic options as the construction of honest, professional public services is the true objective of the State.